2008
DOI: 10.1002/eat.20522
|View full text |Cite
|
Sign up to set email alerts
|

Dialectical behavior therapy for clients with binge‐eating disorder or bulimia nervosa and borderline personality disorder

Abstract: This provides promising pilot data for larger studies utilizing DBT for BED or BN and BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
0
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 32 publications
(40 reference statements)
4
85
0
5
Order By: Relevance
“…In the present study, the remission rate was higher (53.8%) than in treatments targeting either BPD (Harned et al, 2008) or BN (Johnson & Dennis, 1990;Wagner et al, 2006), ranging from 10.5% to 38%. These results support previous findings (Chen et al, 2008;Palmer et al, 2003) indicating that a modified DBT program can decrease BEE and lead to remission in some of the participants with BN. However, the present study adds to previous findings that improvements can be achieved in the long term in a larger, more disturbed sample.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the remission rate was higher (53.8%) than in treatments targeting either BPD (Harned et al, 2008) or BN (Johnson & Dennis, 1990;Wagner et al, 2006), ranging from 10.5% to 38%. These results support previous findings (Chen et al, 2008;Palmer et al, 2003) indicating that a modified DBT program can decrease BEE and lead to remission in some of the participants with BN. However, the present study adds to previous findings that improvements can be achieved in the long term in a larger, more disturbed sample.…”
Section: Discussionsupporting
confidence: 93%
“…No statistical analyses were conducted. Recently, a 6-month outpatient DBT program was conducted for 5 women with BED and 3 with BN as well as a comorbid BPD (Chen, Matthews, Allen, Kuo, & Linehan, 2008). One woman reported three inpatient stays due to AN, BN, and drug abuse.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several preliminary studies have shown that DBT may be a valuable intervention for ED patients with comorbid BPD and those with chronic ED symptoms. [24][25][26][27] As described by others, these data suggest that patients with severe EDs and additional comorbid diagnoses may require more comprehensive interventions. 1,2 In light of these findings, and with the aim of further exploring the efficacy of DBT for complex patients with EDs, the Multidiagnostic Eating Disorder-DBT (MED-DBT) Program was developed and is currently being evaluated in a specialized outpatient treatment center (see Ref.…”
Section: Introductionsupporting
confidence: 69%
“…These modules are designed to help individuals develop more adaptive methods of serving these functions. This treatment was initially developed to treat suicidal and nonsuicidal self-injury (Linehan, 1993a(Linehan, , 1993b) but has been successfully adapted for those with substance use disorders (Linehan et al, 1999), as well as bulimia nervosa (Chen, Matthews, Allen, Kuo, & Linehan, 2008;Safer, Telch, & Agras, 2000 and binge eating disorder (BED, Chen et al, 2008;Telch, 1997;Telch, Agras, & Linehan, 2001. Similarly, acceptance and commitment therapy (ACT) is based on the idea that maladaptive behaviors function as a way of avoiding emotional experience (Hayes, Strosahl, & Wilson, 1999;Hayes, Wilson, Gifford, Follette, & Strosahl, 1996) and these concepts have also been applied to the treatment of eating disorders (see Wilson, 1996Wilson, , 2004.…”
Section: Discussionmentioning
confidence: 99%